Peningkatan Pengetahuan tentang Pemanfaatan Buah Nanas untuk Mencegah Anemia Remaja di Madrasah Aliyah Negeri 1 Muaro Jambi - Hayati, Fatihatul; Maharani, Sri (Universitas Baiturrahim, 2024)
The prevalence of anemia in Indonesia among teenagers is 32%, which means that 3-4 out of 10 Indonesian teenagers suffer from anemia. Low intake or entry of iron and other nutrients into the body, for example vitamin A, vitamin C, folate, riboflavin, B12, and errors in consuming iron, for example when consuming iron together with other substances, can interfere with the process of iron absorption. . Ascorbic acid is one of the components that can trigger the strongest absorption of iron. Pineapples, which belong to the Bromeliaceous family, are a fruit that can increase iron absorption in the intestine. Pineapple plants have long been cultivated by farmers in Jambi Province, this plant is cultivated on a commercial scale in Muaro Jambi Regency. One way to increase health knowledge is by providing education. Education can be done using various media, one of which is an online pocket book (e-booklet). This community service activity was carried out for 30 teenagers who were students at MAN 1 Muaro Jambi from September 2022 to February 2023. The solution given was to provide health education regarding the use of pineapple to prevent adolescent anemia using the counseling method. Knowledge is assessed through the results of filling out a questionnaire. Monitoring and evaluating activities using the One Group Pretest and Post-test Design approach. The expected output target is increased knowledge between before and after being given education. The result of the service was an increase in knowledge after being given education on pineapple fruit to prevent anemia, so that young women can make good use of local plants to overcome anemia.